Similarity and Differences of the Concubine Character in the Novel Wives and Concubines and the Earth of Mankind - Xuc Lin (Bina Nusantara University, 2009)
Wives and Concubines and The Earth of Mankind showed us a situation where women is treated as animals and sold to a man. The moral standard of being concubine is to obey her master. In The Earth of Mankind, Nyai Ontosoroh took us to see her transformation process from a woman who obeyed her master into her master became dependant on her. And, on the contrary in Wives and Concubine, Song Lian, from a woman who protected her dignity changed into losing her personality in order to get the love from the master. Nyai Ontosoroh from a weak woman changed into powerful woman, but Song Lian from quite powerful changed into a woman with mental disorder. Nyai Ontosoroh’s transformation happened because she grasped a good opportunity to study new knowledge, western civilization and modernization. And Song Lian had new-style education but has not experienced self-awakening yet, did not have the concept of “earning your own living”, she did not have courage to step on a new path.